TO ASSESS THE EFFECTIVENESS OF CORRECTION OF DYSBIOSIS OF THE ORAL MUCOSA IN PATIENTS WITH VIRAL GLOSSITIS - Serazetdinova, A.R.; Sultanova, N.I.; Postnikov, M.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: To evaluate the effectiveness of the correction of dysbiosis of the oral mucosa in patients with viral glossitis. Material and methods: The main group consisted of 40 patients with a diagnosis of glossitis due to EBV. There were 30 women, 10 men, the age of patients - from 32 to 68 years. The control group consisted of 38 patients with chronic recurrent herpetic stomatitis, of which 20 were women and 18 were men aged 47 to 70 years. Results: For successful treatment of the initial disease or if other pathology of the oral mucosa is suspected of fungal, bacterial, viral nosology, a microbiological examination of the smear taken from the oral mucosa is necessary. Identification of existing dysbiosis will help to avoid mistakes in choosing a treatment regimen and timely prevent the generalization of infection, the development of complications. Correction of a dysbiotic state requires a gentle attitude to the macroorganism and should be limited to the choice of certain bacteriophages, local immunomodulating drugs, referral to appropriate specialists and further substitution therapy with symbiotic drugs. Conclusions: The selected scheme for correcting dysbiosis of the oral mucosa by bacteriophages is clinically and laboratory effective and absolutely sparing compared to a similar scheme in combination with antimicrobial agents.